Physical Evaluation of the Asian Blepharoplasty Patient - Suhk, Jeong Hoon; Kiranantawat, Kidakorn; Nguyen, Anh H. (Seminars in Plastic Surgery, 2015)
In contrast with Caucasian blepharoplasty, which is usually done for rejuvenation purposes, eyelid surgery for Asians is mainly done for cosmetic reasons. Here the authors present preoperative evaluation methods of Asian eyelids to overcome anatomical variations and determine the right aesthetic options. Proper selection of the most suitable operative methods guarantees optimal surgical results.
Keywords: Asian eyelid anatomy; Asian eyelid; eyelid anatomy; Asian eyelid morphology; Asian blepharoplasty; Asian double crease; Asian oculoplastic surgery; epicanthoplasty; blepharoptosis; eyelids